Vitamin E supplementation modifies adaptive responses to training in rat skeletal muscle. (October 2014) - Venditti, P.; Napolitano, G.; Barone, D.; Di Meo, S.
Abstract Aim of the present study was to test, by vitamin E treatment, the hypothesis that muscle adaptive responses to training are mediated by free radicals produced during the single exercise sessions. Therefore, we determined aerobic capacity of tissue homogenates and mitochondrial fractions, tissue content of mitochondrial proteins and expression of factors (PGC-1, NRF-1, and NRF-2) involved in mitochondrial biogenesis. Moreover, we determined the oxidative damage extent, antioxidant enzyme activities, and glutathione content in both tissue preparations, mitochondrial ROS production rate. Finally we tested mitochondrial ROS production rate and muscle susceptibility to oxidative stress. The metabolic adaptations to training, consisting in increased muscle oxidative capacity coupled with the proliferation of a mitochondrial population with decreased oxidative capacity, were generally prevented by antioxidant supplementation. Accordingly, the expression of the factors involved in mitochondrial biogenesis, which were increased by training, was restored to the control level by the antioxidant treatment. Even the training-induced increase in antioxidant enzyme activities, glutathione level and tissue capacity to oppose to an oxidative attach were prevented by vitamin E treatment. Our results support the idea that the stimulus for training-induced adaptive responses derives from the increased production, during the training sessions, of reactive oxygen species that stimulates the expression of PGC-1, which is involved in mitochondrial biogenesis and antioxidant enzymes expression. On the other hand, the observation that changes induced by training in some parameters are only attenuated by vitamin E treatment suggests that other signaling pathways, which are activated during exercise and impinge on PGC-1, can modify the response to the antioxidant integration.